A TALE OF TWO EURO-ZONES. BANKS’ FUNDING, SOVEREIGN RISK AND UNCONVENTIONAL MONETARY POLICIES - FULLI-LEMAIRE, Nicolas (Journal of Advanced Studies in Finance; Vol 5 No 1 (2014): JASF Volume V, Issue 1(9), Summer, 2014, 2014)
The admission by the Greek government on October 18, 2009, of large-scale accounting fraud in its national accounts sparked an unprecedented sovereign debt crisis that rapidly spread to the Eurozone’s weakest member states. As the crisis increasingly drove a wedge between a seemingly resilient Eurozone core and its faltering periphery, its first collateral victims were the private banks of the hardest-hit sovereigns. They were rapidly followed by the rest of the Eurozone’s banks as a result of their large exposure to not only their home country’s sovereign debt, but also to the debt securities of other member states. Measuring each bank’s precise exposure to every sovereign issuer became a key issue for credit analysis in the attempt to assess the potential impact of a selective sovereign default if worse came to worst. Yet, finding that information in a timely manner is hardly an easy task, as banks are not required to disclose it. Building on the efficient market hypothesis in the presence of informed traders, we tested the sensitivity of each of the largest Eurozone private banks’ CDSs to sovereign CDSs using a simple autoregressive model estimated by time-series regressions and panel regressions, comparing the results to news releases to assess its reliability. Eventually, we used the Oaxaca Blinder decomposition to measure whether the unconventional monetary policies, namely the LTRO and the OMT, that the ECB has implemented to stem the crisis have helped banks directly or whether banks were actually helped by the reduction in sovereign CDS spreads.